2019
DOI: 10.15252/embj.2019101515
|View full text |Cite
|
Sign up to set email alerts
|

Non‐canonical AUX / IAA protein IAA 33 competes with canonical AUX / IAA repressor IAA 5 to negatively regulate auxin signaling

Abstract: The phytohormone auxin controls plant growth and development via TIR1-dependent protein degradation of canonical AUX/IAA proteins, which normally repress the activity of auxin response transcription factors (ARFs). IAA33 is a non-canonical AUX/IAA protein lacking a TIR1-binding domain, and its role in auxin signaling and plant development is not well understood. Here, we show that IAA33 maintains root distal stem cell identity and negatively regulates auxin signaling by interacting with ARF10 and ARF16. IAA33 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(39 citation statements)
references
References 61 publications
0
39
0
Order By: Relevance
“…The discrepancy between Aux/IAA stabilization and DR5 upregulation might be due to the modulation of auxin concentration induced by biosynthesis and by polar auxin transport; however, it might also be related to alternative auxin signaling pathways that regulate auxin-responsive genes in parallel with the canonical TIR1/Aux/IAA-dependent pathway. The alternative pathway involves the auxin-mediated C-terminal cleavage of transmembrane kinase1 (TMK1), which contributes to the regulation of auxin responsive genes in the hypocotyl, LRs, and RAM [ 77 , 78 , 79 , 80 ]. Moreover, experiments with high spatiotemporal resolution have shown that root growth inhibition was dependent on TIR1/AFB signaling and Aux/IAA stability, but independent of transcriptional regulation [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy between Aux/IAA stabilization and DR5 upregulation might be due to the modulation of auxin concentration induced by biosynthesis and by polar auxin transport; however, it might also be related to alternative auxin signaling pathways that regulate auxin-responsive genes in parallel with the canonical TIR1/Aux/IAA-dependent pathway. The alternative pathway involves the auxin-mediated C-terminal cleavage of transmembrane kinase1 (TMK1), which contributes to the regulation of auxin responsive genes in the hypocotyl, LRs, and RAM [ 77 , 78 , 79 , 80 ]. Moreover, experiments with high spatiotemporal resolution have shown that root growth inhibition was dependent on TIR1/AFB signaling and Aux/IAA stability, but independent of transcriptional regulation [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between non-canonical AUX/IAAs and ARFs may also be regulated at the level of posttranscriptional modifications, and phosphorylation driven by TRANSMEMBRANE KINASE1 (TMK1) and MITOGEN-ACTIVATED PROTEIN KINASE14 (MPK14) was found to modulate the repressor function of non-canonical AUX/IAAs. Interestingly, AUXIN BINDING PROTEIN1 (ABP1), an apoplast-localized auxin receptor, may induce activation of the TMK1/MPK14-signaling pathway [ 27 , 28 ]. Although IAA20 and IAA30 were not revealed in the embryo proper at the 8-cell stage [ 29 ], Llavata–Peris and coworkers suggested that IAA33, another non-canonical AUX/IAA, was expressed in all cells until the late globular stage [ 30 ].…”
Section: Multi-level Regulation Of Hd-zip ⅲ and Ap2-domain Transcription Factorsmentioning
confidence: 99%
“…In Arabidopsis, auxin binds directly to AtTIR1 and initiates auxin responses by regulating the degradation of Aux/IAA proteins (Lv et al, 2020). Because MdTIR1 was predicted to interact with MdIAA14, MdIAA28, MdIAA29, MdIAA43, and MdIAA46 in the hormone-related sub-subnetwork (Figure 5A), we hypothesized that MdTIR1 mediates root growth by promoting MdIAA degradation in apple.…”
Section: Malus Domestica Transport Inhibitor Resistant 1 Promotes the Degradation Of Mdiaasmentioning
confidence: 99%
“…As the auxin concentration increases, auxin binds to TIR1 to induce the rapid degradation of Aux/IAAs. This releases transcriptional activator ARFs from repression and leads to the subsequent transcriptional activation of auxin-responsive genes that regulate plant growth and development (Lv et al, 2020).…”
Section: Introductionmentioning
confidence: 99%